RELEVANSI KEWAJIBAN SERTIFIKASI HALAL BAGI PELAKU USAHA DENGAN MAQASHID SYARIAH - Mustatho, Mustatho; Ruslan, Ruslan (Islamic Family Law, STAI Sangatta Kutai Timur, 2024)
Initially, halal certification in Indonesia was taken over by the Indonesian Ulema Council (MUI) which is a civil society movement that received support from the state. However, after the issuance of the Halal Product Assurance Law (JPH Law), the authority for halal certification was transferred to the Halal Product Assurance Agency (BPJPH). This study aims to describe halal obligations for business actors, and their relevance to Maqashid Sharia. The method in this study is literature research that seeks to describe research from books, primary sources are corroborated with secondary sources, then analyzed and tested through triangulation of data sources and methods. The results of this study conclude that the obligation of halal certification helps business actors to gain public trust in the products they sell, as well as for people to be calmer in consuming every product that has a certificate. The relevance to Maqashid Sharia is very strong because with products that have been certified halal, the five main goals of sharia are fulfilled, namely preserving religion, preserving soul, preserving intellect, preserving descendants and preserving property.